Realizing MPEG-4 video transmission over wireless Bluetooth link via HCI - Chong, Hooi Chia; Beg, Mirza Salim (IEEE, 2003)
Video over wireless communication (VoW) has a lot of potential applications in home and office environment. The emergence of two new technologies, namely Bluetooth and MPEG-4, will prove useful in implementing VoW. Video transmission over wireless channel can be made possible by transmitting MPEG-4 bit streams over Bluetooth channels. This paper presents the implementation details of MPEG-4 coded video transmission over Bluetooth (MPEG4BT) via Host Controller Interface (HCI). A detailed set of testing scenarios and results obtained after actual video transmission are presented in this paper.